The role of non-volatile chemicals of floral rewards in plant-pollinator interactions - Leonhardt, Sara Diana; Chui, Shao Xiong; Kuba, Kenneth (Basic and applied ecology, 2024)
The interaction between plants and pollinators has intrigued scientists for centuries. While it continues to be [a] subject of ongoing research in basic and applied ecology, we tend to ignore that plant-pollinator interactions are largely driven by chemistry. For example, the amounts and composition of various chemical compounds determine flower colour, the attractiveness of scent and the nutritional value of floral rewards. In this perspective article, we focus on the chemistry of pollen and nectar. We discuss differences in the function, diversity and variation of compound groups that are considered macro- and micronutrients for pollinators as well as in non-nutritive plant secondary metabolites (PSM). We highlight that effects of and pollinator responses to different compounds vary strongly among pollinator species and (groups of) compounds. Moreover, we challenge the commonly applied separation between toxic (e.g. several PSMs) and beneficial (e.g. most nutrients) compounds and point to a dose-dependent toxicity across compounds. We finally provide a list of open questions for future research. We draw particular attention to the unknown effects that interactions between plant-produced compounds and externally applied compounds (e.g. pesticides, pollutants) may have on the plant-pollinator mutualism.